Longitudinal Volumetric Brain Changes in Autism Spectrum Disorder Ages 6–35 Years. Issue 1 (7th November 2014) - Lange, Nicholas; Travers, Brittany G.; Bigler, Erin D.; Prigge, Molly B.D.; Froehlich, Alyson L.; Nielsen, Jared A.; Cariello, Annahir N.; Zielinski, Brandon A.; Anderson, Jeffrey S.; Fletcher, P. Thomas; Alexander, Andrew A.; Lainhart, Janet E.
Abstract : Since the impairments associated with autism spectrum disorder (ASD) tend to persist or worsen from childhood into adulthood, it is of critical importance to examine how the brain develops over this growth epoch. We report initial findings on whole and regional longitudinal brain development in 100 male participants with ASD (226 high‐quality magnetic resonance imaging [MRI] scans; mean inter‐scan interval 2.7 years) compared to 56 typically developing controls (TDCs) (117 high‐quality scans; mean inter‐scan interval 2.6 years) from childhood into adulthood, for a total of 156 participants scanned over an 8‐year period. This initial analysis includes between one and three high‐quality scans per participant that have been processed and segmented to date, with 21% having one scan, 27% with two scans, and 52% with three scans in the ASD sample; corresponding percentages for the TDC sample are 30%, 30%, and 40%. The proportion of participants with multiple scans (79% of ASDs and 68% of TDCs) was high in comparison to that of large longitudinal neuroimaging studies of typical development. We provide volumetric growth curves for the entire brain, total gray matter (GM), frontal GM, temporal GM, parietal GM, occipital GM, total cortical white matter (WM), corpus callosum, caudate, thalamus, total cerebellum, and total ventricles. Mean volume of cortical WM was reduced significantly. Mean ventricular volume was increased in the ASD sample relative to the TDCs across the broad age range studied. Decreases in regional mean volumes in the ASD sample most often were due to decreases during late adolescence and adulthood. The growth curve of whole brain volume over time showed increased volumes in young children with autism, and subsequently decreased during adolescence to meet the TDC curve between 10 and 15 years of age. The volume of many structures continued to decline atypically into adulthood in the ASD sample. The data suggest that ASD is a dynamic disorder with complex changes in whole and regional brain volumes that change over time from childhood into adulthood. Autism Res 2015, 8: 82–93 . © 2014 International Society for Autism Research, Wiley Periodicals, Inc.